2014
DOI: 10.1007/s12178-013-9200-0
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of glenoid bone defects in shoulder instability with autologous bone

Abstract: Bone defects, both at glenoid and at the humeral side are a frequent sequel of anterior shoulder instability. Although the transfer of the coracoid process (Latarjet, Bristow procedures) has gained popularity in treating the glenoid defect, equal results can be achieved with the use of a bone graft, for which mainly a graft of the iliac crest is used. Recently, arthroscopic procedures have been developed, leaving the subscapularis muscle largely intact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“… 22 Changes such as improved fixation of the grafts with screws and attention to the positioning of the graft have improved the procedure's results. 8 , 23 Two recent systematic reviews on different glenoid bony augmentation procedures for chronic anterior shoulder instability confirmed that the Eden-Hybinette procedure had clinical outcomes very similar to those of the Bristow-Latarjet technique, with a lower rate of neurologic complications. 24 , 25 It should be noted, however, that the harvest site morbidity causes 10% to 25% of complications (mainly chronic pain and dysesthesia of the lateral cutaneous femoral nerve).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 22 Changes such as improved fixation of the grafts with screws and attention to the positioning of the graft have improved the procedure's results. 8 , 23 Two recent systematic reviews on different glenoid bony augmentation procedures for chronic anterior shoulder instability confirmed that the Eden-Hybinette procedure had clinical outcomes very similar to those of the Bristow-Latarjet technique, with a lower rate of neurologic complications. 24 , 25 It should be noted, however, that the harvest site morbidity causes 10% to 25% of complications (mainly chronic pain and dysesthesia of the lateral cutaneous femoral nerve).…”
Section: Discussionmentioning
confidence: 98%
“…The Rowe shoulder score was good or excellent, and the global rate of osteoarthritis was 44% 22 . Changes such as improved fixation of the grafts with screws and attention to the positioning of the graft have improved the procedure's results 8, 23. Two recent systematic reviews on different glenoid bony augmentation procedures for chronic anterior shoulder instability confirmed that the Eden-Hybinette procedure had clinical outcomes very similar to those of the Bristow-Latarjet technique, with a lower rate of neurologic complications 24, 25.…”
Section: Discussionmentioning
confidence: 99%
“…When facing this problem, several treatment options have been suggested. [4][5][6][7] The Latarjet coracoid transfer has become quite popular over the past few years. 6 Outcomes are comparable to other bone block procedures with the Latarjet techniques having the lowest re-dislocation but the highest complication rate.…”
mentioning
confidence: 99%
“…[4][5][6][7] The Latarjet coracoid transfer has become quite popular over the past few years. 6 Outcomes are comparable to other bone block procedures with the Latarjet techniques having the lowest re-dislocation but the highest complication rate. 8,9 Other bone block procedures include iliac crest bone, J-span, the Eden-Hybinette procedure, and more recently tibial allografts.…”
mentioning
confidence: 99%
See 1 more Smart Citation